Green Synthesis of Silver Nanoparticles from Ocimum sanctum Linn. and Study of Their Antioxidant Activity - Pathak, Ishwor; Niraula, Muna; Sharma, Khaga Raj; Thapa, Prakash; Oli, Hari Bhakta; Kalauni, Surya Kant (Amrit Research Journal, 2024)
Green synthesis of silver nanoparticles (AgNPs) has gained considerable attention due to their unique properties and wide-ranging applications. This study focuses on the synthesis of AgNPs utilizing the methanol extract of aerial parts of Ocimum sanctum Linn., commonly known as holy basil or Tulsi. The synthesis process is environmentally friendly and offers a sustainable alternative to conventional methods. Characterization of the synthesized AgNPs is performed using various techniques, including field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD). The results demonstrate the successful synthesis of AgNPs with distinct morphologies and crystalline structures. Additionally, the antioxidant activity of the AgNPs is evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, with ascorbic acid as a reference standard. The synthesized OCE-AgNPs exhibit an IC50 value of 49.71 μg/mL, which is close to that of the standard ascorbic acid (41.34 μg/mL). The results of this study highlight the potential applications of OCE-AgNPs in biomedical and pharmaceutical fields.